Extract of Azadirachta indica (Neem) leaf induces apoptosis in 4T1 breast cancer BALB/c mice. - Othman, Fauziah; Motalleb, Gholamreza; Lam, Sally Tsuey; Rahmat, Asmah; Fakurazi, Sharida; Chong, Pei Pei (Royan Institute (ACECR), Tehran, 2011)
OBJECTIVE: Azadirachta indica (Neem) has been used traditionally for many centuries. Some impressive therapeutic qualities have been discovered. However, the therapeutic effect of neem leaf extract in 4T1 breast cancer has not been documented. The purpose of the present study is to investigate the therapeutic effect of ethanolic Neem leaf extract in an in vivo 4T1 breast cancer model in mice. MATERIALS AND METHODS: A total of 84 female BALB/c mice were divided randomly into 7 groups (3 non-cancerous groups and 4 cancerous groups) consisting of 12 mice per group. The 3 non-cancerous groups were normal mice treated with 0.5% of Tween 20 in phosphate buffer saline (PBS) (NC), 250 mg/kg Neem (N250) or 500 mg/kg Neem (N500). The 4 cancerous groups were; cancer controls treated with 0.5% of Tween 20 in PBS (CC), and cancerous mice treated with 0.5 µg/mL tamoxifen citrate (CT), 250 mg/kg Neem leaf extract (CN 250) or 500 mg/kg Neem leaf extract (CN 500). Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assays were used to evaluate apoptosis (cell death) in the breast cancer tissues. SPSS software, version 14 was used for statistical analysis. Statistical significance was defined as p≤0.05. Non parametric analysis of variance (ANOVA) was performed with the Kruskal Wallis test for the TUNEL assays. Parametric data among the groups was compared using ANOVA. RESULTS: TUNEL assays showed that the CN 250 and CN 500 groups had a higher incidence of apoptosis compared with the cancer controls. CONCLUSION: The findings showed that neem leaf extract induces apoptosis in 4T1 breast cancer BALB/c mice.